Measuring empowerment in WASH: Ghana (SEI Policy brief) - Bori, S; Dickin, S; Bisung, E; Atengdem, J (Stockholm Environment Institute, 2019)
Improved monitoring tools are key to ensuring that gender and social equality outcomes receive priority attention within policy and practice related to WASH. The Empowerment in WASH Index (EWI) is a new assessment and monitoring tool that aims to close the evidence gap on the links between WASH interventions and the empowerment and wellbeing of individuals. Challenges identified by EWI go beyond infrastructure-oriented solutions and address more structural (e.g. social norms, governance systems) changes. This policy brief provides an overview and key findings of the EWI study in Asutifi North District, Ghana and presents recommendations drawn from dissemination workshops held at a District Level Learning Alliance Platform (DLLAP) at the Asutifi North District Assembly and a National Level Learning Alliance Platform in Accra.